Analysis of Online Taxi (Uber) in Islamic Economy Perspective - Sutono Sutono (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractThe rise of the online taxi business (uber) has caused various reactions, both positive and negative, because it has an impact on the congestion of other transportation companies that have resulted in losses, and it is very noticeable in orange taxi companies, blue bird taxi and many more companies taxi that is the same as the two companies. For this reason, this study aims to find out in depth the practices and operations of Uber online taxi and to find out in depth the Islamic economic law review of an online taxi. This research is descriptive qualitative to explore the problems that occur by using interviews as a data analysis technique. Based on the results of the study, the legal status of uber's online taxi operations has been officially licensed and operates on a conditional basis. This term is if the conditions are fulfilled, then it can operate, and if it cannot be fulfilled, the permits are refused or may not operate. While regarding the legal status of uber companies with taxi drivers is a contract of sale and buy, and can be called musyarakah contract (cooperation). Whereas, the status for customers and uber companies is an ijarah contract (rent) and can also be a sale and buy contract.Keywords: online taxi, uber, customer, Islamic economy law